Neurophysiological Influence of Musical Training on Speech Perception - Shahin, Antoine J. (Frontiers in Psychology, 2011)
Does musical training affect our perception of speech? For example, does learning to play a musical instrument modify the neural circuitry for auditory processing in a way that improves one’s ability to perceive speech more clearly in noisy environments? If so, can speech perception in individuals with hearing loss, who struggle in noisy situations, benefit from musical training? While music and speech exhibit some specialization in neural processing, there is evidence suggesting that skills acquired through musical training for specific acoustical processes may transfer to, and thereby improve, speech perception. The neurophysiological mechanisms underlying the influence of musical training on speech processing and the extent of this influence remains a rich area to be explored. A prerequisite for such transfer is the facilitation of greater neurophysiological overlap between speech and music processing following musical training. This review first establishes a neurophysiological link between musical training and speech perception, and subsequently provides further hypotheses on the neurophysiological implications of musical training on speech perception in adverse acoustical environments and in individuals with hearing loss.